Design and Optimisation of Marine two-stroke Diesel Engine Piston - Ifunanya Stella Ezeoye; Mohammad Orangian (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2019)
In the cylinder of conventional compression ignition engine, temperature distribution and stress variation set up in the entire piston due to the inherent nature of combustion. This project will investigate causes and effects of high gas pressure and temperature on marine two-stroke diesel engine piston. Investigation has shown that stress-related piston damages play a dominant role mainly due to mechanical and thermal stress or combination of both. The simulation parameters that will be considered in this report are piston material, combustion temperature and combustion pressure. In the present study, conventional marine two-stroke diesel engine piston will be modelled using Autodesk Inventor software. The working condition of the piston will be simulated based on the selected parameters using finite element analysis method to analyze the magnitude of mechanical stresses acting on the piston. The piston will be re-designed using a material superior to the conventional piston material and will be optimized by reducing the stresses acting on the piston. Two materials will be used in the analysis after which the results will be compared and the best will be proposed. The structure and stress analysis (mechanical, thermal and thermal-mechanical stress) of the design will be modelled using the software mentioned earlier.